Liposomal Form of the Echinochrome-Carrageenan Complex - Irina M. Yermak; Vladimir I. Gorbach; Valery P. Glazunov; Anna O. Kravchenko; Natalya P. Mishchenko; Evgeniya A. Pimenova; Viktoria N. Davydova (Marine Drugs, 2018)
Inclusion of drugs in liposomes offers the potential for localized and sustained delivery to mucosal surfaces. The inclusion of the carrageenan matrix with echinochrome A ((Ech)—the active substance of the drug Histochrome) in liposomes was studied. According to the spectral characteristics, Ech was not oxidized and retained stability after encapsulation in the liposomes and the lyophilization process. Loading the liposomes with negatively charged polysaccharide results in the increase in the zeta potential to more negative values (from −14.6 to −24.4 mV), that together with an increasing in the sizes of liposomes (from 125.6 ± 2.5 nm to 159.3 ± 5.8 nm) propose of the formation of the polymer coating on liposomes. The interactions of liposomes with porcine stomach mucin was determined by the DLS and SEM methods. The changes in the zeta-potential and size of the mucin particles were observed as the result of the interaction of liposomes with mucin. To evaluate the mucoadhesive properties of liposomes and the penetration of Ech in the mucosa, a fresh-frozen inner surface of the small intestine of a pig as a model of mucous tissue was used. Polysaccharide-coated liposomes exhibit very good mucoadhesive properties −50% of Ech remains on the mucosa.